The Effect of Flashcard-Assisted Congklak Game Innovation on Reading Literacy of 5-6 Years Old Children: An Experimental Study - Maharani, Aprilia Devita; Tasuah, Neneng (Universitas Pendidikan Mandalika, 2025)
Development in reading literacy is the most important thing in the process of child development at an early age. For this reason, there is a need for innovation in learning to improve students' reading literacy learning process. One of them is by using the traditional game media congklak. This study aims to increase the level of reading literacy learning of students at the age of 5-6 years. The approach used in this study is a quantitative approach with a Pre-Experimental Designs design where this method uses one class to be given treatment. The subjects used were all children aged 5-6 years with a total of 36 children. Data collection was carried out by researchers by means of observation, interviews, as well as documentation. Then the test carried out is by using validity test, reliability test, normality test, and N-Gain. The results showed that, with the learning media, the game of congklak can increase students' interest in learning. Not only that, but it also makes learning so varied and fun. This can provide an opportunity to develop children's literacy at an early age.